Disability and Islamic Law in Indonesia: Beyond the Rukhṣah - Maftuhin, Arif (Studia Islamika, 2023)
In the past decade, Indonesia has witnessed a surge in interest in exploring the intersection of Islam and disabilities. This trend began with a seminar at UIN Sunan Kalijaga in 2011, leading to numerous research initiatives and publications, culminating in the publication of separate Fikih Difabel by three prominent Islamic institutions. However, these works often treat disabilities as exceptions, relying heavily on exceptions (rukhṣah) rather than developing comprehensive solutions that integrate people with disabilities as full and equal members of the community. This article examines the approaches and limitations of those three Fikih Difabel and proposes a more inclusive Fikih Difabel. It advocates adoption a holistic paradigm encompassing approach, definitions, methods, and accessibility, emphasizing the need to move beyond the rukhṣah. Employing a contextual discussion on ṭahārah to illustrate my proposed approach, this article aims to encourage a more practical and comprehensive framework for addressing disabilities within fiqh in Indonesia.